Alcohol abuse in eastern Nepal: a review of studies - Shakya, Dhana Ratna (Health Renaissance, 2013)
Alcohol abuse is common in eastern Nepal, rather reported remarkably high. Hence, various aspects of this problem have been the topic of search, study, survey and research in this part of the country, both in community and clinical settings. This article aims to review the journal articles published, research projects presented in scientific forum or conferences, thesis articles submitted and other research works related to alcohol from eastern Nepal coming into the knowledge of the author. The basis of this review were medical journals including Health Renaissance (HR), abstract books of various medical meets, internet search and personal communication with various departments of BP Koirala Institute of Health Sciences (BPKIHS), a prominent centre for the research projects carried out both by students and faculty members in this area. Overarching the objective would be to point out some important needs and areas for future research studies in next article. Health Renaissance, January-April 2013; Vol. 11 No.1; 74-82 DOI: http://dx.doi.org/10.3126/hren.v11i1.7607